Acute toxicity, 28-day repeated-dose toxicity and toxicokinetic study of timosaponin BII in beagle dogs. Issue 9 (2nd September 2022) - Zhou, Fei; Liu, Bao-Feng; Wang, Can; Zhang, Jie; Dong, Guo-Ming; Jin, Hong-Tao; Ma, Bai-Ping; Zhong, Xiao-Ming
Abstract: The safety evaluation of timosaponin BII (TBII) in beagle dogs with toxicokinetic study was performed. For the acute oral toxicity study, the minimum lethal dose (MLD) of TBII was more than 2000 mg/kg and suggested the characteristics of absorption saturation. For the 28-day repeated dose oral toxicity and toxicokinetic studies, there was no significant effect on all test parameters except for prolonged APTT in the 60 and 180 mg/kg groups, which recovered after withdrawal. The increase of drug exposure of 180 mg/kg group was not proportional to the increase of administration dose, showing the characteristics of absorption saturation.